The Politics of Exchange Rates in Developing Countries Political Cycles and Domestic Institutions - Setzer, Ralph; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2006)
This book considers the issue of exchange rate policymaking from a political economy perspective. It illustrates both theoretically and empirically how domestic political and institutional incentives shape exchange rate policies in developing countries. Modelling policymakers$1 (Bpreferences as endogenous, the book answers questions as the following: What influences the relative value that a country puts on fixed versus floating regimes? Why do governments, during certain episodes, deviate from an officially announced exchange rate regime? How do policymakers$1 (Bexchange rate preferences change during election periods? The empirical analysis is based on a panel survey of 47 countries and thereby provides insights on how political and institutional conditions typically affect exchange rate policy.s
General introduction -- The normative and the positive view on exchange rate policy -- Fear of floating and fear of pegging: How important is politics? -- Political uncertainty and speculative attacks -- Developing a theory of currency peg duration -- The determinants of fixed exchange rate regime duration: A survival analysis -- Political cycles and the real exchange rate -- Conclusion and discussion.
Keywords: Macroeconomics; International economics; Development economics; Economics; Macroeconomics/Monetary Economics//Financial Economics; Development Economics; International Economics; Electronic books